Unemployment in Iraq: Reality and Solution (مجلة المنصور, 2022)
Among the requirements of achieving an economic development in Iraq is consolidating efforts for ideal employment of labor forces and stopping unemployment according to details specified by the developing policy itself . That in turn reflects the ability of these policies to stop unemployment . This is done after a full identification of supply and demand on labor force and its reflections on the national income, and the effects of these factors on the cons-umption and saving, (or investment ). This is to reach a better redistribution of labor forces according to the planning relationship between the expansion of employees and the development of production factors . Hence, the present research deals with the demographic reality, and the orientations of both employment and unemployment . Then, it is proposed a problem- treatment procedure represented by modifying the structure of both labor force and training programs.